VERBAL VALENCY FROM THE STANDPOINT OF VERBAL CO-OCCURRENCE WITHIN A COMPLEX SENTENCE IN SLOVENE (Philological Studies, 2019)
The paper discusses the valency features and particularities of those cases in which two or more verbs co-occur within a complex sentence. Valency verbal semantic groups provide the basis of the treatment, which later on focuses on an analysis of the possibilities for and the varying degrees of the valent co-existence of verbs from different but limited verbal semantic groups within the same sentence.
Keywords: valency, valency verbal semantic groups, syntax of text